化简tan(2派-a)tan(3派-a)/tan(-派+a)tan(3派-a)tan(-a-派)
1个回答
原式=-tana*(-tana)/[tana*(-tana)*tana]
=-cota
相关问题
已知f(a)=sin^2(派-a)*cos(2派-a)*tan(-派+a)/sin(-派+a)*tan(-a+3派)求一
已知tan(a+5派)=m,化简:[sin(a-3派)+cos(派-a)]/
已知:f(a)=sin(-派-a)分之sin(派-a)cos(2派-a)tan(-a+2分之3派) tan(-a-派)
化简:sin(2派-x)tan(派+x)cot(-x-派)/tan(3派-x)cos(派-x)
化简:cos(x-派)tan(x-2派)tan(2派-x)/sin(派+X)
若tan(A+B)=3/5,tan(B-派/4)=1/4.则tan(A+派/4)=?
己知tan(-a-4派/3)=5则tan(派/3+a)值为
tan(-5派/4)=?tan(-2派/3)=?
如果tan(a+b)=3/4,tan(a-派/4)=1/2,那么tan(b+派/4)的值是
tan(-17派/6)=-tan17派/6=-tan(5派/6+2派),-tan(5派/6+2派)是怎么来的,